IMPLIKASI REPOSISI MILITER PASCA ORDE BARU TERHADAP KETAHANAN NASIONAL - M. Yusuf A.R. (GANEC SWARA, 2022)
This study aims to determine the implications of TNT repositioning on National Resilience. The research method uses descriptive qualitative research. The data are sourced from books, journals, articles, or newspaper news.The results of the study show that the implications of military repositioning on national security are evident from the growth of other components of national security, especially civil society in the form of civil society. However, figures from the military still have political influence and are accepted by civil society.In conclusion, the repositioning of the TNI has implications for the growth of new forces such as political parties, community organizations, and NGOs that can support national security. However, these forces are not strong enough because of the democratization process in Indonesia. Indonesia itself is not mature enough.,